Bryant & may and the bleeding heart eaudiobook Bryant and may series, book 11. - Fowler, Christopher (Bryant & May, 2014)
London's wiliest detectives, Arthur Bryant and John May, are back on the case in this fiendishly clever new mystery. And when a cemetery becomes the scene of a crime, neither secrets—nor bodies—stay buried. Romain Curtis sneaks into St. George's Gardens one evening with his date, planning to show her the stars. A centuries-old burial ground, the small, quiet park is the perfect place to be alone. Yet the night takes a chilling turn when the two teenagers spy a strange figure rising from among the tombstones: a corpse emerging from the grave. Suffice it to say that wherever there's a dead man walking, Bryant and May and the Peculiar Crimes Unit are never far behind. As the PCU investigates the sighting, a second urgent matter requires their unusual brand of problem-solving. Seven ravens have gone missing from their historic home in the Tower of London, and legend has it that when the ravens disappear, England will fall. Bryant has been tasked with recovering the lost birds, but when Romain is suddenly found dead, the two seemingly separate mysteries start to intertwine and point to a plot more sinister than anyone could ever imagine.